User Acceptance Test of Computer-Assisted Problem-Based Learning Assessment Tool (CAPBLAT) - Muhammad Qomaruddin; Azizah Abdul Rahman; Noorminshah A.Iahad (Intelektual Pustaka Media Utama, 2014)
Problem-based Learning (PBL) is an instructional design method that is used by many lecturers to create more efficient and meaningful learning experiences. PBL emphasizes the lecturer in facilitating in collaborative learning. They conventionally play a little role in the formal assessment process. Peer-assessment and self-assessment are the most frequent methods of assessment employed by the lecturers in conducting PBL approach. This paper presents acceptance testing of a computer-based tool for peer-assessment and self-assessment in PBL approach, which called Computer-Assisted Problem-Based Learning Assessment Tool (CAPBLAT). The tool was designed to assist a lecturer in conducting PBL teaching method and assess students learning progress. Two PBL classes participated in the testing of the tool. During the study, questionnaires were administered to students. The results concerning the assessment tool acceptance demonstrate that using CAPBLAT in the PBL assessment process received better acceptance from both the students and lecturers.